ANALISIS KARAKTERISTIK TEKANAN PEMBAKARAN MESIN DIESEL MENGGUNAKAN SOFTWARE SOFTHALIZA 8.7 - Moch. Syaiful Anwar; Mochamad Shaleh (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2024)
This study analyzes the combustion pressure characteristics of Diesel Engine #8 using SoftHaliza 8.7 software through the Pressure Combustion Analysis (PCA) method. The research aimed to evaluate the effect of fuel additive usage on combustion pressure performance in each cylinder. Data collection was conducted by measuring combustion pressure before and after the application of fuel additive under stable engine operating conditions.The analysis results showed that the use of fuel additive improved the combustion characteristics in all cylinders. The average combustion pressure increased from 56.50 bar before additive application to 67.99 bar after additive application, with an average deviation of 11.49 bar. The highest pressure increase occurred in Cylinder 4 with a deviation of 17.3 bar, while the lowest increase was observed in Cylinder 5 with a deviation of 8.9 bar. In addition, the combustion pressure graphs generated by SoftHaliza 8.7 indicated smoother and more stable expansion curves after additive application, reflecting a more complete combustion process and improved combustion efficiency.Overall, SoftHaliza 8.7 proved effective for monitoring combustion pressure characteristics, identifying combustion conditions in each cylinder, and supporting predictive maintenance activities to improve the reliability and operational performance of diesel engines.